2021
DOI: 10.1111/apha.13703
|View full text |Cite
|
Sign up to set email alerts
|

Chronodisruption by chronic jetlag impacts metabolic and gastrointestinal homeostasis in male mice

Abstract: Aim: Chronodisruption desynchronizes peripheral clocks and leads to metabolic diseases. Feeding cues are important synchronizers of peripheral clocks and influence rhythmic oscillations in intestinal microbiota and their metabolites. We investigated whether chronic jetlag, mimicking frequent time zone travelling, affected the diurnal fluctuations in faecal short-chain fatty acid (SCFA) levels, that feed back to the gut clock to regulate rhythmicity in gut function. Methods: Rhythms in faecal SCFAs levels and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 83 publications
2
42
0
Order By: Relevance
“…Several studies show that chronodisruption (genetic or environmental) disrupts the rhythms in food intake in mice [14,16,32]. This is in agreement with our results showing that the JL AL mice consumed equal amounts of calories during the day and night.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Several studies show that chronodisruption (genetic or environmental) disrupts the rhythms in food intake in mice [14,16,32]. This is in agreement with our results showing that the JL AL mice consumed equal amounts of calories during the day and night.…”
Section: Discussionsupporting
confidence: 93%
“…We previously showed that microbial metabolites such as SCFAs are known to entrain circadian clock gene expression in the colonic mucosa [16,42]. Therefore, circadian clock gene expression was studied in the mucosa of the distal colon over 24 h in Ctrl RF, JL AL, and JL RF mice.…”
Section: Trf Partially Prevented Changes In Clock Gene Expression Of Colonic Mucosa Caused By Chronic Jetlagmentioning
confidence: 99%
See 3 more Smart Citations